Refractory Acute Interstitial Nephritis in the Setting of Nivolumab Therapy - Antonio Faieta; Tavis Dancik (Case Reports in Nephrology)
A 65-year-old male patient with metastatic CCRCC developed steroid-dependent, grade 3 AIN secondary to nivolumab weeks after its initiation that resulted in 3 hospitalizations with acute renal failure. The patient was started on MM and his AIN was successfully controlled after a 2-year period of follow-up. Refractory renal AIN resulting from PD-1 inhibitor use is rare, and its successful treatment with mofetil mycophenolate with a 2-year follow-up in a patient with metastatic CCRCC has not been reported. This case is important because not only was his renal irAEs controlled but also long-term treatment with MM did not result in progression of metastatic disease.